Policies for Artificial Intelligence in Higher Education: A Call for Action - Ally, Mohamed; Mishra, Sanjaya (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2024)
This paper highlights the importance of artificial intelligence (AI) policies in higher education institutions and presents a step-by-step process for adopting institutional policies. Emphasizing the inevitable implications on AI in teaching and learning, this paper also discusses key policy areas for consideration by the stakeholders and lists the competencies that will influence appropriate policy development.